A new co-processing mode of organic anaerobic fermentation liquid and municipal solid waste incineration fly ash. (September 2022) - Zhang, Jiazheng; Mao, Yanpeng; Wang, Wenlong; Wang, Xujiang; Li, Jingwei; Jin, Yang; Pang, Dongjie
Graphic abstract: Highlights: Synergistic treatment of fly ash with AFWLs, reduced chlorine content to below 1%. Brewing wastewater reduced the chlorine content of MSWI-FA to 0.91%. The washing process affects the heat treatment of fly ash. The melting point of MSWI-FA washed by the best process, decreased by nearly 30 ℃. Washing pretreatment changed MSWI-FA from hazardous waste to cement raw meal. Abstract: A new co-processing mode of waste liquid from anaerobic fermentation of organic wastes and municipal solid waste incineration fly ash (MSWI-FA) dechlorination is reported in this paper. Taking acetic acid, the most common organic acid in anaerobic fermentation systems, as the representative of anaerobic fermentation organic acids, the improvement of the dechlorination effect and the mechanism of washing MSWI-FA with low concentrations of organic acid lotion were explored. The chlorine content of MSWI-FA was reduced to 0.82% after the optimal process washing pretreatment. Three anaerobic fermentation waste liquids (AFWLs) were used to verify that the chlorine content of MSWI-FA could be reduced to less than 1%, and the dechlorination effect of brewery wastewater, which reduced the chlorine content of MSWI-FA to 0.91%, was the best at this. The influence of the washing process on MSWI-FA pyrolysis was reflected in the whole process. The release of chloride decreased and the weight loss was mainly due to the release of CO2 . The melting point of MSWI-FA, washed by the optimal process, was reduced by nearly 30 ℃, and only 0.06% chlorine remained after calcination at 1100 ℃, which was extremely beneficial in reducing the release of trace elements in MSWI-FA during heat treatment, and for the preparation of cement raw meal.